Adoption of agro-weather information sources for climate smart agriculture among farmers in Embu and Ada'a districts of Kenya and Ethiopia. (September 2019) - Oladele, OI; Gitika, MP; Ngari, F; Shimeles, A; Mamo, G; Aregawi, F; Braimoh, AK; Olorunfemi, OD
Adaptation strategies are considered to be an effective measure to build resilience to the effects of climate change. The agro-weather tools for adaptation to climate smart agriculture were implemented as a pilot project in Embu and Ada'a Districts of Kenya and Ethiopia respectively. Random sampling technique was used to select 360 and 171 farmers from the population of project's beneficiaries in Kenya and Ethiopia and data collection was carried out with the use of a questionnaire. The overall results show that farming experience and impact of agro-weather information were significant determinants of the use of all the tools. Ownership/access, extension contact, frequency of extension contact and extension agency were significant determinants of the use of short message service (SMS), newsletter, and radio while group membership was a significant determinant of the use of SMS, newsletter, and interactive voice response. The significance of these variables stresses their need in the planning and policy formulation for the use of agro-weather tools for information dissemination.